Identifying the Critical Domain of LL-37 Involved in Mediating Neutrophil Activation in the Presence of Influenza Virus: Functional and Structural Analysis - Tripathi, Shweta; Wang, Guangshun; White, Mitchell; Rynkiewicz, Michael; Seaton, Barbara; Hartshorn, Kevan (PLOS ONE, 2015)
The human cathelicidin LL-37 has been shown to play a role in host defense against influenza A viruses (IAV) through direct antiviral effects and through modulating inflammatory responses to infection. We recently showed that LL-37 increases neutrophil respiratory burst and neutrophil extracellular trap (NET) responses to IAV through engaging formyl peptide receptor 2 (FPR-2). In this paper we show that a fragment of LL-37, GI-20, which is composed of the central helical segment of the peptide, has similar effects as LL-37 on neutrophil activation. In addition to increasing respiratory burst and NET responses of the cells to IAV through an FPR-2 dependent mechanism, it reduces neutrophil IL-8 production to IAV (also like LL-37). The N-terminal fragment, LL-23, did not have similar effects. Both GI-20 and LL-37 increase neutrophil intracellular calcium levels and their ability to increase neutrophil activation responses was calcium dependent and partially inhibited by pertussis toxin. These studies show that the central helix of LL-37 retains the ability of LL-37 to modulate neutrophil responses through FPR-2. Based on our findings we developed a homology model of FPR-2 and performed docking experiments of LL-37 and GI-20 with the receptor.